Mitochondria: A Common Target for Genetic Mutations and Environmental Toxicants in Parkinson’s Disease - Helley, Martin P.; Pinnell, Jennifer; Sportelli, Carolina; Tieu, Kim (Frontiers in Genetics, 2017)
Parkinson’s disease (PD) is a devastating neurological movement disorder. Since its first discovery 200 years ago, genetic and environmental factors have been identified to play a role in PD development and progression. Although genetic studies have been the predominant driving force in PD research over the last few decades, currently only a small fraction of PD cases can be directly linked to monogenic mutations. The remaining cases have been attributed to other risk associated genes, environmental exposures and gene-environment interactions, making PD a multifactorial disorder with a complex etiology. However, enormous efforts from global research have yielded significant insights into pathogenic mechanisms and potential therapeutic targets for PD. This review will highlight mitochondrial dysfunction as a common pathway involved in both genetic mutations and environmental toxicants linked to PD.